2022
DOI: 10.1111/maps.13814
|View full text |Cite
|
Sign up to set email alerts
|

Karavannoe: Mineralogy, trace element geochemistry, and origin of Eagle Station group pallasites

Abstract: Karavannoe is a pallasite found in Russia in 2010. The mineralogy, chemistry, and oxygen isotopic composition indicate that Karavannoe is a member of the Eagle Station Pallasite (ESP) group. Karavannoe contains mostly olivine and subdued interstitial Fe,Ni‐metal. Zoned distribution of FeO in small, rounded grains of olivine and FeO and Al2O3 in chromite shows that the cooling rate of the melt was fast during the crystallization of the round olivine grains. Siderophile element distribution and correlations of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, natural plessite in iron and stony iron meteorites can exhibit mixed morphological characteristics. For example, the plessite in Mangui (Figure 1) has round kamacite grains in duplex plessite, and the plessite in NWA 6369 (IAB) was defined as the spheroidized plessite (Teplyakova et al., 2011), but it is actually duplex plessite. Moreover, it should be noted that the same morphological type of plessite can be formed through various mechanisms and require distinct formation conditions and processes; an example being net plessite observed in L group chondrites and irons (see discussion on net plessite below).…”
Section: Discussionmentioning
confidence: 99%
“…However, natural plessite in iron and stony iron meteorites can exhibit mixed morphological characteristics. For example, the plessite in Mangui (Figure 1) has round kamacite grains in duplex plessite, and the plessite in NWA 6369 (IAB) was defined as the spheroidized plessite (Teplyakova et al., 2011), but it is actually duplex plessite. Moreover, it should be noted that the same morphological type of plessite can be formed through various mechanisms and require distinct formation conditions and processes; an example being net plessite observed in L group chondrites and irons (see discussion on net plessite below).…”
Section: Discussionmentioning
confidence: 99%
“…It can be inferred that Hoba might have experienced a moderate shock event. Teplyakova et al (2011) reported the spheroidized plessite in NWA 6369 (IAB). Although some taenite within the plessite exhibits nearly circular shapes, it strictly represents duplex plessite.…”
Section: Possible Applications In Ironmentioning
confidence: 99%